Pengaruh Microlearning Berbasis Website Terhadap Kemampuan Literasi Numerasi Siswa Kelas VI Pada Materi Pecahan - Ketut Suardina; I Putu Suardipa; I Komang Wahyu Wiguna (Cetta: Jurnal Ilmu Pendidikan, 2026)
The low numerical literacy skills of Indonesian students, particularly in fraction materials at the elementary school level, form the primary background of this research. This study aims to maximize students' numerical literacy potential through the implementation of a microlearning approach integrated into an innovative website. The method used is a quasi-experimental design with a Pretest-Posttest Control Group Design, involving 45 sixth-grade students, with 22 students in the experimental group and 23 students in the control group. Data were collected using Higher Order Thinking Skills (HOTS) oriented essay tests and analyzed using the Independent Sample T-Test to identify differences between groups, as well as the N-Gain test to measure skill improvement. The results show a significant difference in numerical literacy skills between the experimental and control classes, with a significance value of 0.000 < 0.05. The numerical literacy gain in the experimental class is in the medium category (0.534), while the control class is in the low category (0.179). Based on simple linear regression analysis, the website-based microlearning approach contributes a 47.5% influence (coefficient of determination) to students' numerical literacy skills. This study concludes that the integration of concise, focused, and interactive learning content within a digital platform is effective in improving critical reasoning and contextual problem-solving skills in fraction materials.